Commercial Incense: Compound Analysis and Its Molecular Docking Studies as Anxiolytic Agents - Apsari, Cintya Nurul; Ujiantari, Navista Sri Octa; Rohmah, Zuliyati; Utami, Setyowati Triastuti; Suma, Artania Adnin Tri; Gusnaniar, Niar (Biology, Medicine, & Natural Product Chemistry, 2024)
In the context of Indonesian culture, incense has been traditionally utilized in various rituals. Incense possesses a calming impact and has the potential to reduce anxiety. This physiological response stems from the interplay of chemical components within incense and receptors associated with relaxation, specifically GABAA. This research aims to explore the interaction between substances found in commercially incenses with the GABAA receptors. The compounds of incense were identified through Gas Chromatography-Mass Spectrometry (GCMS) analysis. And there were 54 compounds identified from the 5 incense samples. Next, the ligands employed for docking studies were compounds predicted to traverse the blood-brain barrier (BBB). There were 31 compounds potential of crossing the blood-brain barrier (BBB). Docking results indicated that the majority of tested compounds exhibited notably lower S-scores during receptor interaction, suggesting their potential as anxiety-relieving agents. Furthermore, molecular docking outcomes highlighted that 9-Octadecenoic acid (Z)-, 2-hydroxy-1-(hydroxymethyl)ethyl ester showed the lowest S-score (-6.573). These findings imply that odorant and other volatile organic compounds (VOCs) present in incenses possess the ability to function as anxiety-reducing (anxiolytic) agents, potentially assisting in anxiety treatment.